Isotherm Study, Adsorption Kinetics and Thermodynamics of Lead Using Combination Adsorbent of Chitosan and Coffee Ground Activated Carbon - Nisa Nurhidayanti Nisa; Aris Dwi Cahyanto (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
The presence of lead metal in water naturally due to its mobility can cause the nature of water to become toxic and endanger the environmental ecosystem because it bioaccumulates in the food chain. The purpose of this study was to study the maximum adsorption capacity through an isotherm model, to determine the rate of adsorption kinetics in the use of chitosan and coffee grounds adsorbents in reducing lead concentrations in industrial wastewater and to study its thermodynamic magnitude. The research method was carried out using experiments in the laboratory followed by quantitative data analysis to determine the isotherm model and adsorption kinetics. The results showed that the adsorption isotherm follows the Langmuir isotherm model with a correlation coefficient of 0.9970 with a maximum adsorption capacity of 1.0511 mg.g-1 which indicates that chemical adsorption occurs in the mono layer with a homogeneous distribution of adsorption sites with adsorption energy. constant and negligible interactions between lead metal molecules (adsorbate). Study of lead adsorption kinetics using chitosan-activated carbon coffee grounds following the Weber-Morris/intra-particle diffusion model with a correlation coefficient of 0.9920 with a diffusion rate of 76.512 g.mg-1.hour-1 indicating that intra-particle diffusion is the rate step limiting in the overall biosorption process. Negative ΔGo values ​​indicate that the adsorption reaction takes place spontaneously, ΔHo of 0.8130 indicates an endothermic reaction, and ΔSo of 4.1888 indicates an increase in the randomness of the adsorption process at the adsorbent interface and lead during adsorption.